IMPACT OF LEADERSHIP STYLES AMONG HEAD NURSES ON LEVEL OF JOB SATISFACTION AMONG STAFF NURSES - Abdelhafiz, Ibrahim Mubarak; Alloubani, AlaDeen Mah’d; Klaledeh, Mahmmoud; Mutari, Naif; Almukhtar, Mohammad Musa (European Scientific Journal, ESJ, 2015)
Background: According to the studies made previously, it has been shown that the underlying basis of any communication between employees and leaders are the leadership styles. They also help improve the process of work in an organization. Aim: The purpose of this study is to demonstrate the influence that leadership styles of different nurse leaders have on the satisfaction of work. Methods: We selected three different private hospitals situated in Amman, and we had used descriptive and quantitative methods in the study. Results: Among the participated hospitals, the highest score was gained by transformational leadership. The second highest was transactional leadership, followed by passive-avoidant. The job satisfaction level was seen to be quite high in this study. There was a positive relation between job satisfaction (r= 0.371**) and total score of transformational leadership (TRL). The transactional leadership score (TAL) also had a positive relation with respect to job satisfaction which was (r= 0.389**). However, the overall relationship between job satisfaction and passive-avoidant leadership (PAL) was seen to be negative in the result (r= -0.241**). Conclusion: It was concluded that a nurse’s job satisfaction is increased by greater enhancement of transformational leadership attitude which further results in a greater nurse supply.